Comparison of Depression Case Incidence on Adi Sumarmo Boyolali Airport Employees between Apron and Non-Apron Region Employees - Pamungkas, Wahyu (Nexus Kedokteran Komunitas, 2016)
Background: Noise is one of the most often encountered stressor to human being. Aircraft noise is considered to be the most annoying transportation noise, due to its noise level and intermittent nature. Noise will interfere with the working of the brain, especially in its endocrine regulation. It is estimated that in 2020 depression will be the problem and will be the second global burden after ischemic heart disease. The most common cause of depression is dysregulation of Hypothalamus-Pituitary-Adrenal (HPA) axis. The aim of this research is to compare depression case incidence on Adi Sumarmo Boyolali airport employees between apron and non-apron region employees. Methods: This research is an analytical cross-sectional study, conducted in Adi Sumarmo Airport Boyolali. The research was conducted in November 2014. The independent variable was workplace noise that divided into 2: apron area (81.3 WECPNL noise level) and non-apron area (64.14 WECPNL noise level). While the dependent variable was depression measured by Beck Depression Inventory II questionnaire. Samples were Adi Sumarmo Airport Boyolali employees with at least a year of the working time, no having psychiatric disorders, no having both chronic dieases and congenital diseases, no having hearing loss, no wearing ear model of personal protective equipment, no experiencing death of sib in last 3 months, LMMPI score with ânoâ answers < 10, and were willing to be respondents and approved informed consent. Total of 86 samples were obtained by consecutive sampling after selected based on inclusion and exclusion criteria. It divided into 2 groups. Each consists of 43 employees. The data were analyzed by chi-square test. Result: The prevalence of depression was 46.5% in the apron area and 20.9% in the non-apron area. Chi-square test showed that there was a statistically significant difference in depression score among two groups (p = 0.012; p<0.05). Conclusion: There was significant difference of depression case incidence on Adi Sumarmo Boyolali Airport employees between apron and non-apron employees. Keywords: Adi Sumarmo Airport, aircraft, depression, noise.Â